HUBUNGAN KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN CSR TERHADAP NILAI PERUSAHAAN LOGAM DAN MINERAL TAHUN 2019- 2023 - Pirmansyah, Pirmansyah; Uli. S , Desti Monika; Zurman, Zurman; Dewi, Dessy Kumala; Maharani, Maharani (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to analyse the impact of managerial ownership, institutional ownership, and corporate social responsibility on the valuation of metal and mineral enterprises from 2019 to 2023. This research employs a quantitative methodology with secondary data as its source. The sample in this study consisted of 8 participants selected using purposive sampling. The employed data analysis technique was multiple linear regression. The study's results indicate that independent variables, including management ownership, institutional ownership, and corporate social responsibility, concurrently affect the dependent variable, which is firm value. Managerial ownership and corporate social responsibility significantly influence firm value, whereas institutional ownership does not have a notable impact on company value.